Peran Kriminalitas Sebagai Pemoderasi Antara Kemiskinan dan Pengangguran Terhadap Laju Pertumbuhan Ekonomi - Aji Priambodo (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
This study uses the Moderated Regression Analysis (MRA) method which aims to analyze the effect of the crime rate as a moderating variable between the poverty rate and the unemployment rate on the rate of economic growth, and partially analyze poverty and unemployment on the growth rate in districts and cities in Central Java. The data used is secondary data in the form of panel data using the Eviews 10 software in 35 regencies and cities in Central Java Province in 2018-2021. The results of this study are poverty has a negative and significant effect on the rate of economic growth, unemployment has a negative and significant effect on the rate of economic growth, crime as a moderating variable between poverty and the rate of economic growth as a Predictor Moderator. Crime can strengthen the relationship between poverty and economic growth. Crime as a moderating variable between unemployment and the rate of economic growth as a Quasi Moderator. Crime can strengthen the relationship between unemployment and economic growth.